Business guide to world trading system - International Trade Centre UNCTAD/WTO (ITC GenevaCH, 1999)
Reviews developments that have taken place between 1996 and 1999. Explains the role of WTO as a forum for negotiations and as an organisation for settling trade disputes. Presents rules applicable to trade in goods as embodied in GATT 1994 and its associate Agreements. Reviews the main features of the General Agreement on Trade in Services and the related commitments of member countries. Explains rules applicable to government procurement and state trading and describes the provisions of the Agreement on Trade-Related Aspects of Intellectual Property Rights. Provides an overview of issues under discussion in the six trade-related subject areas added to the WTO work programme.